Service-oriented SCADA and MES supporting petri nets based orchestrated automation systems - Colombo, Armando W. (2013)
The fusion of mechatronics, communication, control and information technologies has allowed the introduction of new automation paradigms into the production environment. The virtualization of the production environment facilitated by the application of the service-oriented architecture paradigm is one of major outcomes of that fusion. On one side, service-oriented automation works based on exposition, subscription and use of automation functions represented by e.g. web services. On the other side, the evolution of traditional industrial systems, particularly in the production area, as a response to architectural and behavioural (functional) viewpoints of the ISA95 enterprise architecture, where a close inter-relation between SCADA, DCS and MES systems facilitate the management and control of the production environment. Automation functions are increasingly performed by the composition and orchestration of services. Among other methods, the application of formal Petri net based orchestration approaches is being industrially established. This paper presents the major characteristics that such a Petri net based orchestration presents when it is developed, implemented and deployed in an industrial environment